Perjanjian Syariah pada Lembaga Keuangan Syariah - Saidurrahman, Saidurrahman (Program Pascasarjana UIN Sunan Ampel Surabaya, 2012)
Although Syariâah is considered by many as the ideal form of socialâas well as financial- order, it is nonetheless not immune from practical and perhaps technical problems, so to speak. With regards to the Syariâah finance, cases on the ground show that transaction involving dispute by different parties does often occur. This dispute has nothing to do with the Syariâah itself indeed, but with the way it is applied. Syariâah however anticipates this dispute to happen, concerning which this paper is interested. It is concerned with discussing this anticipation and in what way does Syariâah offer the way-out to resolve such a dispute in matters relating to financial contract. The paper argues that the ability of such system as Syariâah to resolve problems and offer solution for disputes can be an indicator whether the system can be judged as an ideal or not. One of the techniques that the Syariâah has offered in dealing with dispute is what it calls Musyawarah (negotiation); a technique that in fact has been regulated in the Indonesian law. This technique will also be investigated in this paper.